1997
DOI: 10.1046/j.1365-2559.1997.2800874.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and interphase cytogenetic analysis of desmoid tumours

Abstract: These results suggest that a subgroup of desmoid tumours at risk of recurrence may be hypervascular lesions associated with trisomy 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…Hoos et al [44] did not find nuclear staining for Ki-67 in 24 of the examined cases of aggressive fibromatosis. Neither Kouho et al [45] detected any cells (or were few) with nuclear staining of Ki-67 in 24 desmoid cases.…”
Section: Discussionmentioning
confidence: 83%
“…Hoos et al [44] did not find nuclear staining for Ki-67 in 24 of the examined cases of aggressive fibromatosis. Neither Kouho et al [45] detected any cells (or were few) with nuclear staining of Ki-67 in 24 desmoid cases.…”
Section: Discussionmentioning
confidence: 83%
“…Several authors have suggested that failure to detect these trisomies by conventional cytogenetic methodologies may be explained by rapid overgrowth of the trisomic cells by diploid populations. 7,8 Fletcher et al 8 and Kouho et al 17 have also observed a correlation between the presence of trisomy 8 and an increased risk of recurrence. In the current study, trisomy 8 was detected in two desmoid tumors; one was a recurrent lesion, and the other was from a patient who was lost to follow-up.…”
Section: Cytogeneticsmentioning
confidence: 92%
“…Cytogenetic and molecular cytogenetic analyses of desmoid tumors are few and are particularly sparse or are nonexistent for desmoplastic fibroma, periosteal desmoid tumor, osteofibrous dysplasia, and fibrous dysplasia. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] To determine the frequency of trisomy 8 and trisomy 20 in additional desmoid tumor cases and to examine their presence in related fibrous lesions of bone, both standard karyotypic analysis and molecular cytogenetic analysis were performed on 22 representative specimens. …”
mentioning
confidence: 99%
“…Multiple studies described the clonal nature of desmoids pointing at malignant capacities that place these tumors into the category of fibroblastic malignancies (8,(39)(40)(41)(42)(43). The presence of trisomy 8 and/or 20 (which are non-random clonal aberrations acquired during neoplastic progression) and the proportion of cells with these trisomies vary greatly between desmoid tumor specimens (range 0 to 25%) (8,(42)(43)(44). It can be therefore concluded that trisomies 8 and 20 contribute to neoplastic aberrations in a wide spectrum of pathologic fibrous proliferations, without any distinction between benign or malignant (8,42,43).…”
Section: The Neoplastic Nature Of Desmoidsmentioning
confidence: 99%
“…In comparison to other malignancies, desmoids were found with a relatively low expression of metastasis promoting extracellular matrix proteins such as osteopontin and osteonectin, suggested to be the reason for the inability to disseminate (39,45). Other common malignant tumor markers as Ki-67, pRB or Bcl-2 have not been observed to be upregulated in desmoid tissue (39,43,(46)(47)(48). Appropriate tumor markers may explain the clinical behavior of desmoids, and still need to be identified (10).…”
Section: The Neoplastic Nature Of Desmoidsmentioning
confidence: 99%